ANALISIS SOSIOLINGUISTIK TERHADAP REPRESENTASI IDEOLOGI ANTIPOLITIK UANG DALAM IKLAN LAYANAN MASYARAKAT TVRI“TOLAK POLITIK UANG” - Oki Erina Mutiara Bintang; Esa Aulia Maharani Oktaviana; Muhammad Dimas Kurniawan; Ingghar Ghupti Nadia Kusmiaji (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to analyze language variations in TVRI's Public Service Announcement entitled "Reject Money Politics" to understand the formation of moral messages and anti-money politics ideologies through linguistic choices. Language variations in advertisements not only function as an information medium but also as a communication strategy that adapts messages to the characteristics of diverse audiences. This study uses a qualitative descriptive approach with sociolinguistic analysis based on Chaer and Agustina's language variation theory. Data were obtained through transcriptions of verbal utterances in advertisement videos uploaded to TVRI's official YouTube channel, then classified into three categories: popular mass language, legal language, and persuasive language. The results show that popular mass language is used to create closeness with the public through familiar greetings and simple diction. Legal language serves to emphasize the authority of election regulations through legal terms and criminal sanctions. Meanwhile, persuasive language is used to encourage attitude change through direct invitations and affirmation of moral values. These three language variations complement each other in building public awareness and strengthening the message of rejecting the practice of money politics in order to maintain the integrity of democracy